Yo ho ho, Halloween! - Ryan, Pam Muñoz (Ryan, Pam Muñoz. Tony Baloney., 2016)
Halloween is coming! This year, Tony Baloney wants to stand out in the crowd at the school Halloween parade. But can he keep his costume intact until the day of the parade?